Fulfillment of Basic Needs for Children with Special Needs: A Case Study of Children with Autism at SLB Negeri 1 Makassar - Agus, Alamsyah; Nurkumala, Muhlisani (Journal of Community Services and Engagement: Voice of Community (VOC), 2025)
Children with special needs, particularly those with autism, require comprehensive support to ensure that their basic physiological, emotional, social, and self-fulfillment needs are met within the educational setting. Ensuring the fulfillment of these needs is crucial for their growth, learning development, and long-term independence. This study examines the fulfillment of basic needs among children with autism at SLB Negeri 1 Makassar based on Maslow’s hierarchy of needs. A qualitative approach was employed using a case study design, with data collected through observations, in-depth interviews, and documentation. Informants included teachers, the school principal, and parents. The findings reveal that the basic needs of children with autism are largely fulfilled through individualized learning programs, structured daily activities, emotional support from teachers, and active parental involvement. The school also provides a safe learning environment, specialized facilities, and vocational activities that foster students’ potential and independence. Nevertheless, several challenges remain, including the limited availability of professional staff, inadequate facilities, and the diverse characteristics of the students. To address these challenges, the school implements individualized approaches, reward systems, and strong collaboration between the school and families. In conclusion, the fulfillment of basic needs for children with autism at SLB Negeri 1 Makassar has been carried out effectively through structured and collaborative strategies, although further efforts are required to enhance facilities and strengthen cross-sector cooperation.